SISTEM PAKAR UNTUK DIAGNOSA PENYAKIT GINJAL DENGAN MENGGUNAKAN CERTAINTY FACTOR - PUTRA, AGE (STMIK Kaputama, 2019)
With the rise of kidney disease sufferers, the factors that most influence lifestyle and the environment, kidney disease is not a hereditary disease, with certainty factor systems can find out patients early on, this system is built on a web basis, so users can easily access and choose symptoms that are felt about kidney disease information.